2015
DOI: 10.1089/cbr.2015.1884
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Use of Transhepatic Arterial Chemoembolization and Bipolar Radiofrequency Ablation in the Clinical Therapy of Hepatocellular Carcinoma

Abstract: This retrospective study investigated the clinical application of sequential therapy with transarterial chemoembolization (TACE) and CT-guided radiofrequency ablation (RFA) using a bipolar needle in treating hepatocellular carcinoma (HCC) tumors of different sizes. The study included patients (N = 46) with HCC from Shengjing Hospital of China Medical University who had received TACE and RFA from November 2012 to November 2013. Eligible patients had an Eastern Cooperative Oncology Group (ECOG) score of 0-1, a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that lipiodol deposition in HCC tumour might be used as an imaging indicator to evaluate TACE therapeutic efficacy [21][22][23][24]. By identifying the lipiodol deposition patterns on post-TACE CT, we first calculated the proportion of lipiodol deposition in all enrolled patients and categorized them into two different groups with 50% as cut-off according to previous reports [25][26][27] (Fig. 5A).…”
Section: Correlation Between Lipiodol Deposition and Cnvs In Pre-tace...mentioning
confidence: 99%
“…Previous studies have demonstrated that lipiodol deposition in HCC tumour might be used as an imaging indicator to evaluate TACE therapeutic efficacy [21][22][23][24]. By identifying the lipiodol deposition patterns on post-TACE CT, we first calculated the proportion of lipiodol deposition in all enrolled patients and categorized them into two different groups with 50% as cut-off according to previous reports [25][26][27] (Fig. 5A).…”
Section: Correlation Between Lipiodol Deposition and Cnvs In Pre-tace...mentioning
confidence: 99%
“…Histologic studies performed with liver specimens from patients who underwent RFA as bridge treatment before transplantation showed that the presence of large (≥3 mm) abutting vessels results in a decrease of about 50% in the rate of complete tumor necrosis because of the heat loss due to perfusion-mediated tissue cooling in the area to be ablated [25]. The methods to overcome the heat sink effect include pharmacologically decreasing blood flow [26,27,28,29], temporary vascular balloon occlusion [30,31], and intra-arterial embolization [32,33]. A combination of TACE followed by RFA is the most widely used technique aiming to minimize heat loss due to the heat sink effect, and the effectiveness of this combination treatment has been confirmed by several investigators [34,35,36,37,38,39].…”
Section: Local Ablative Therapymentioning
confidence: 99%
“…A previous study demonstrated that tumor size affected the complete tumor ablation of LA [39]. In fact, tumor size is also a significant factor affecting the local efficacy of ablation in other thermal ablation techniques including RFA and MWA [40][41][42]. Combined RFA and ethanol injection could increase the range of coagulative necrosis and enlarge the ablation volume [43].…”
Section: Discussionmentioning
confidence: 99%